Molecular mechanisms of Sepsis attacking the immune system and solid organs - Yang, Zhaoyun; Gao, Yan; Zhao, Lijing; Lv, Xuejiao; Du, Yanwei (Frontiers in Medicine, 2024)
Remarkable progress has been achieved in sepsis treatment in recent times, the mortality rate of sepsis has experienced a gradual decline as a result of the prompt administration of antibiotics, fluid resuscitation, and the implementation of various therapies aimed at supporting multiple organ functions. However, there is still significant mortality and room for improvement. The mortality rate for septic patients, 22.5%, is still unacceptably high, accounting for 19.7% of all global deaths. Therefore, it is crucial to thoroughly comprehend the pathogenesis of sepsis in order to enhance clinical diagnosis and treatment methods. Here, we summarized four classic mechanisms of sepsis progression, activation of signal pathways, mitochondrial quality control, imbalance of pro-and anti-inflammation response, diseminated intravascular coagulation (DIC), cell death and, presented the latest research findings for each mechanism and identify potential therapeutic targets within each mechanism.